Comparison of salivary and serum IgG and IgA levels with total protein in oral lichen planus - Bokka, Sri Sathya Naga Mallika; Veeravalli, Venkatavishnu; Botta, Sai Lalitha; Kandiraju, Manjunath; Prasanna (International Journal of Clinical Trials, 2025)
Background: Lichen planus is the common dermatologic disease with oral manifestations. It is an immunologically based, chronic, inflammatory, mucocutaneous disorder with undetermined etiology. The role of salivary immunoglobulins in the immunopathogenesis and the clinical course of oral mucosal diseases, have not been yet studied comprehensively. IgG and IgA being the predominant immunoglobulins in normal serum. Secretory IgA constitutes the predominant immunoglobulin isotype in secretions, including saliva. Materials: Followed by informed consent 20 patients diagnosed with Lichen planus are enrolled in the study from the Department of Oral and Maxillofacial Pathology, MNR Dental College and Hospital, Sangareddy. A new particle-enhanced turbidimetric immunoassay using mono-specific sheep antibodies on the SPAPLUS® analyzer is used to determine the soluble antigen concentration (IgG, IgA). Results: The results showed that the mean serum IgG and IgA levels in lichen planus patients is higher when compared with controls. There is a significant difference in the mean IgG and IgA levels levels in both the study groups (<0.001; sig). The current study results showed that the mean salivary IgG and IgA levels in lichen planus patients is elevated compared to controls. A significant difference is found in the mean IgG and IgA levels in patients and controls (<0.001; sig). Conclusion: The results might conclude that elevated levels of serum and salivary IgG and IgA show that humoral immunity is implicated in the pathogenesis of oral lichen planus. Further studies with more number of cases could throw light on the etiology and pathogenesis of the disease.